Structure of the Bighorn Mountain region, Wyoming, from teleseismic receiver function analysis: Implications for the kinematics of Laramide shortening. Issue 9 (8th September 2014) - Yeck, William L.; Sheehan, Anne F.; Anderson, Megan L.; Erslev, Eric A.; Miller, Kate C.; Siddoway, Christine S.
Abstract Basement‐cored uplifts are observed globally and remain an enigmatic feature of plate tectonics due to the fact that, in many cases, they occur distant from a plate boundary. The Laramide Bighorn Arch in Wyoming is an archetypal basement‐involved foreland arch and provides an excellent setting for the investigation of such structures. Previous studies proposed diverse arch formation models; each of which predicts a unique crustal geometry. We use high‐resolution crustal imaging from teleseismic P wave receiver functions to test these models. We obtained our data from 239 three‐component seismometers deployed as part of the Bighorns Arch Seismic Experiment as well as coeval regional Transportable Array stations. A sequential, two‐layer thickness VP/VS (H‐κ) stacking algorithm constrains sediment and crustal structure. Receiver function Common Conversion Point stacking results in 2‐D transect images across the arch. Our results define an upwarp of the crust beneath the central and northern arch that extends into the Powder River Basin, north‐northeast of the arch. The lack of Moho‐cutting faults or a Moho geometry mirroring the arch rules out most shortening models except a crustal detachment model where shortening was accomplished by fault‐propagation folding on a thrust splay ramping off a midcrustal detachment fault. The mismatch between gentle, symmetric Moho and asymmetric Laramide arch geometries and their trends suggests a pre‐Laramide origin for at least a part of the Moho high. This high, perhaps in combination with a lesser degree of Laramide lithospheric buckling, may have caused emergent Laramide thrusting and thus nucleated the Bighorn Arch. Our results suggest that midcrustal detachment can form basement‐involved foreland arches and suggest the hypothesis that preexisting undulations in the Moho may have nucleated individual arches.